PENDIDIKAN, SIKAP, SOSIAL EKONOMI, DAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS KANDANG KOTA BENGKULU - Sanisahhuri Sanisahhuri; Fikitri Marya Sari; Piter Indra Luki (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
Diarrhea is still an important health problem because it is the third contributor to child morbidity and mortality in various countries including Indonesia. This study aimed to study the relationship of education, attitudes, and socio-economics with the incidence of diarrhea in children under five in working area of Kandang Public Health Center Bengkulu. This type of research was Analytical Survey using Cross Sectional design. The population in this study were all mothers who had toddlers and visited Kandang Public Health Center Bengkulu. The sampling technique in this study used Accidental Sampling and obtained sample of 51 mothers of children under five. Data collection in research used primary data obtained from direct interviews with respondents. Data analysis techniques were carried out by univariate and bivariate analysis using the Chi-Square statistical test. The results were obtained: from 51 mothers, there were 18 mothers (35.3%) with toddlers who experienced diarrhea, 22 mothers (43.1%) with basic education, 31 mothers (60.8%) being favorable, 26 mothers (51.0%) had prosperous family socio-economic I. This study showed that there was a significant relationship between maternal education and the incidence of diarrhea in children under the medium category, there was a significant relationship between maternal attitude and diarrhea incidence in toddlers in the medium category, and there was a significant relationship between socio-economic and the incidence of diarrhea in children under five in the tight. Kandang Public Health Center should conduct health education about diarrhea for mothers of children under five in its working area. Keywords: attitude, diarrhea, education, socio-economic